Dynamic biomechanical analysis of transverse patella fracture fixation techniques - Ter, Celestina Ai Wei (Nanyang Technological University, 2024)
Transverse patella fracture accounts for 70% to 90% of patella fractures, which accounts for about 1% of all fractures. The patella serves an important role in providing for the extensor mechanism of the knee and allow for movement. For the continual provision of function of patella, there are several fixation techniques currently in practice. Kirschner wire (K-wire) is the most common technique, however, it often causes discomfort in patients. The objective of this study is to compare the mechanical strength of three fixation techniques: K-wire with cerclage wiring (KW), cannulated screws (CS), and cannulated screws with fibre tape Arthrex (FT). CS and FT are evaluated in comparison to KW, to determine their potential as an alternative to KW. Six samples from each construct underwent cyclic loading ranging from 100 N to 300 N at a frequency of 5 Hz using the Zwick fatigue machine. The fracture gap displacement was analysed using ImageJ. After which, a load to failure test was performed on these samples on the Shimadzu tensile machine at a speed of 5mm/min, with the peak failure load recorded. Results showed that FT exhibited the least fracture displacement gap and highest load to failure, followed by CS, and lastly KW. Significant differences (p < 0.05) were observed in the fracture displacement gap between all constructs. As for the load to failure test, significant differences (p < 0.05) were noted between the KW and CS/FT, while no significant difference (p > 0.05) found between CS and FT. Since CS and FT performed significantly better than KW, they are viable alternatives to mitigate post-operative pain in patients. However, to determine whether CS or FT is a better alternative, more research would need to be done.